Isolation and biological characterization of a basic phospholipase A2 from bothrops jararacussu snake venom - Maruñak, Silvana Licia (2007)
Fil: Maruñak, Silvana Licia. Universidad Nacional del Nordeste. Facultad de Ciencias. Veterinarias; Argentina.